A Call for Research on the Prognostic Role of Follow-Up Histology in Celiac Disease: A Systematic Review - Szakács, Zsolt; Gede, Noémi; Gyöngyi, Zoltán; Solymár, Margit; Csupor, Dezső; Erőss, Bálint; Vincze, Áron; Mikó, Alexandra; Vasas, Andrea; Szapáry, László; Dobszai, Dalma; Balikó, Viktória; et al. (Frontiers in Physiology, 2019)
Background: Convincing evidence is lacking on the benefit of follow-up biopsy in celiac disease. Regardless, achieving mucosal recovery (MR) has remained a desirable goal of therapy. Our aim was to conduct a systematic review to determine whether MR is a protective factor and persisting villous atrophy (PVA) has undesired consequences on long-term outcomes of celiac disease. Methods: Seven databases were searched for articles discussing celiac patients subjected to a gluten-free diet who had a follow-up biopsy, and clinical and laboratory characteristics were reported by follow-up histology (MR vs. PVA). Outcomes included clinical symptoms, mortality, malignant tumors, nutritional parameters, and metabolic bone disease. Comparative and descriptive studies were included. Since data proved to be ineligible for meta-analysis, the evidence was synthesized in a detailed systematic review. Results: Altogether, 31 studies were eligible for systematic review. Studies suggested that persisting symptoms are more frequently associated with PVA than with MR, though a lot of symptom-free patients had PVA and a lot of symptomatic patients achieved MR. The difference was undetectable if symptoms or well-being scores were compared. Mortality and malignant tumors (except for lymphomas in a nationwide registry identifying PVA as a risk factor) seemed independent of follow-up histology. Patients with PVA tended to develop metabolic bone disease more often, though fracture risk remained similar in the groups (except for hip fractures of which PVA was a risk factor). Reports on nutritional markers are only anecdotal, attributing a controversial role to follow-up histology. Conclusions: A lot of celiac patients remain symptomatic despite achieving MR, and, vice versa, PVA patients may be asymptomatic on the long-term. While mortality does not elevate, hip fractures and lymphomas may be more often with PVA than with MR. The limited evidence urges further prognostic studies to be arranged.